The problems of teaching phraseological units in English language - Oblaqulova Dinora Jamshid qizi (Global Scientific Publishing, 2024)
This article deals with the principal difficulties of teaching the phraseological units to ESL students in English. Firstly, problems in the learning process will be stated and explained in a detailed way. Then, proper solutions and practical teaching methods will be provided to teach phraseological phrases to language learners in English classroom. All given information will be supported with clear reasons and accurate examples.
Keywords: phraseological phrases; difficulties; functions